Traumatic abdominal wall hernia associated with necrotizzin fasciitis: A case report - Vera-Portilla, Angel F. (2023)
Traumatic Abdominal Wall Hernia (TAH) is secondary to Closed Abdominal Trauma (TAbC). Defined as a herniathrough a musculofacial defect, without skin penetration, and without evidence of a previous hernia. We present the case of a 48-year-old man who suffered a traffic accident, diagnosed with PAHT and wall fasciitis by means of tomography, who died despite surgical treatment. PAHT is rare, it is the most severe form of abdominal wall injury, and it is associated with Intra-Abdominal Injuries (LIA). The diagnosis can be difficult, and the tomography is the most useful study of imagen. Management generally involves urgent surgical intervention to resolve LIAs; however, the treatment and closure of the defect must be adapted to each patient and the circumstances.